Apical microleakage in teeth filled using lateral condensation technique, single cone and new proposal technique - Paucar-Gutiérrez, Helly (2016)
Objectives: Compare the degree of apical microleakage using three filling techniques: lateral condensa-tion, single cone and a new proposed technique. Materials and method: 36 teeth were prepared with rotary files Mtwo until Nº. 40 / .04 and then be randomly selected using three obturation techniques (G1: lateral condensation technique, G2: single cone; G3: new proposed technique). Subsequently, the teeth are varnished exposing the apical 4mm, dipped in ink and those undergoing the decalcification process following the Protocol of Roberston and measured seepage through a stereoscopic microscope. Comparisons were made with the Kruskal Wallis test. Results: The new proposed technique had a lower rate of microfiltration comparing the lateral condensation technique and single cone. No statistically significant differences between the three obturation techniques. Conclusions: The apical microleakage was similar among the three obturation techniques.